2020
DOI: 10.1101/2020.05.19.104026
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Medial Prefrontal Cortex Interacts with the Anteromedial Thalamus in Motivation and Dopaminergic Activity

Abstract: How does the prefrontal cortex (PFC) regulate motivated behavior? Our experiments characterize the circuits of the PFC regulating motivation, reinforcement and dopamine activity, revealing a novel cortico-thalamic loop. The stimulation of medial PFC (mPFC) neurons activated many downstream regions, as shown by functional MRI. Axonal terminal stimulation of mPFC neurons in downstream regions, including the anteromedial thalamic nucleus (AM), reinforced behavior and activated midbrain dopaminergic neurons. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…However, a recent report suggests that the anterior thalamic nuclei, and in particular the anteromedial thalamic nucleus, may have a hitherto unappreciated role in processes that support instrumental learning ( Yang et al, 2020 ). These authors found that optogenetic stimulation of medial prefrontal cortex terminals within the anteromedial thalamic nucleus supported intracranial self-stimulation, with animals readily acquiring a lever press response to obtain photo-stimulation of these terminal fields.…”
Section: Learning and Attentionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, a recent report suggests that the anterior thalamic nuclei, and in particular the anteromedial thalamic nucleus, may have a hitherto unappreciated role in processes that support instrumental learning ( Yang et al, 2020 ). These authors found that optogenetic stimulation of medial prefrontal cortex terminals within the anteromedial thalamic nucleus supported intracranial self-stimulation, with animals readily acquiring a lever press response to obtain photo-stimulation of these terminal fields.…”
Section: Learning and Attentionmentioning
confidence: 99%
“…These authors found that optogenetic stimulation of medial prefrontal cortex terminals within the anteromedial thalamic nucleus supported intracranial self-stimulation, with animals readily acquiring a lever press response to obtain photo-stimulation of these terminal fields. Interestingly, other thalamic targets of the medial prefrontal cortex only supported modest levels of intracranial self-stimulation (mediodorsal thalamic nucleus) or none at all (nucleus reuniens) ( Yang et al, 2020 ). The same authors then confirmed that the reciprocal connections between the anteromedial thalamic nucleus and medial prefrontal cortex also support intracranial self-stimulation.…”
Section: Learning and Attentionmentioning
confidence: 99%
See 2 more Smart Citations
“…The number of users of short video software continues to grow, and more and more people will watch short videos as a form of leisure and entertainment (Yaqi et al, 2021). The important reason for the popularity of short videos is that the video content stimulates the brain and causes the brain to release dopamine, which makes people continue to search for dopamine secreting content in the ocean of short videos, and ultimately indulge in behavior (Yang et al, 2020). This makes many people unable to resist the short-lived pleasure brought by the software, and the emptiness brought by this happiness will make people even more hope to use the software to have fun (Omar & Dequan, 2020).…”
Section: Impact On Mass Entertainmentmentioning
confidence: 99%